The challenge of pharmaceutical promotion regulation in Malaysia. - Othman, Noordin; Vitry, Agnes I.; Roughead, Elizabeth E. (IIUM Press, 2011)
Information on medicines provided to doctors should be of high quality to support the quality use of medicines. Pharmaceutical promotion is used by pharmaceutical companies to disseminate information about their medicines to doctors. Although the companies claim that promotion offers evidence-based information, research shows that pharmaceutical promotion often provide bias and poor quality of information that may negatively influence doctors' prescribing behaviour. In Malaysia, the pharmaceutical market is highly competitive. It appears that pharmaceutical companies actively promoting their medicines to Malaysian doctors. Given the absence of a comprehensive independent source of prescribing information in Malaysia, Malaysian doctors may be more likely to rely on medicines information provided by pharmaceutical companies. Clearly, pharmaceutical promotional activities in Malaysia need to be effectively regulated. This article will discuss the regulation of pharmaceutical promotion and current policy challenges in Malaysia.